Peran Pemerintah Daerah dalam Mendukung Pariwisata di Era Pasca-Pandemi di Minahasa, Sulawesi Utara, Indonesia - Amalia Arifah; Novel Stefly Assa; Jakub Saddam Akbar (Jurnal Ilmiah Wahana Pendidikan, 2026)
This article examines the role of local government in supporting tourism development in the post-pandemic era in Minahasa and North Minahasa Regencies, North Sulawesi, Indonesia. The COVID-19 pandemic has significantly impacted the tourism sector in this region, reducing tourist visits and hindering economic activities dependent on the tourism industry. Using a qualitative approach with a case study design, this research analyzes how local governments perform their functions as primary drivers, facilitators, and regulators in tourism recovery. The findings reveal five main themes: (1) local government as the primary driver of tourism development; (2) infrastructure development as the foundation for recovery; (3) policy and regulation as a supporting framework; (4) penta-helix collaboration and partnerships as an acceleration strategy; and (5) sustainability and cultural preservation as development principles. This research concludes that post-pandemic tourism recovery in Minahasa requires strong synergy between local government policies, infrastructure investment, digital marketing, financial regulatory intervention, and local community empowerment to achieve sustainable and inclusive recovery.